PERAN POLITISI PEREMPUAN DALAM MEMELIHARA KEHARMONISAN RUMAH TANGGA PERSFEKTIF HUKUM ISLAM (Studi Pada Dewan Pimpinan Daerah Partai Golkar Provinsi Bengkulu) - Haryanto, Haryanto (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2023)
Abstract: The formulation of the problems that will be raised in this study are: 1. What is the role of women politicians in maintaining household harmony in the Regional Leadership Council of the Golkar Party in Bengkulu Province? 2. How is the Islamic Law Review of the role of women politicians in maintaining household harmony in the Regional Leadership Council of the Golkar Party in Bengkulu Province? The type of research used in this study is empirical juridical legal research. This study concludes that: 1. Based on the results of the author’s research, it can be concluded that the role of female politicians in maintaining household harmony in the Regional Leadership Council of the Golkar Party Bengkulu Province is as follows: In serving with her husband, Mrs. Mardensi and Mrs. Mega Sulastri did it intensively every time, Even though as members of the legislature, Ms. Mardensi and Ms. Mega Sulastri are still like other mothers, such as preparing breakfast for her husband and children, preparing all the husband’s needs if there is an outside service. For every holiday, try to travel with the family and cook food according to the tastes of the children and husband. , Give each other attention by giving birthday gifts to husbands and Establishing communication and being honest and open to husbands and creating a pleasant atmosphere in the family. 2. Review of Islamic Law on the Role of Women Politicians in maintaining household harmony in the Regional Leadership Council of the Golkar Party in Bengkulu Province. Basically, Islam does not prohibit women from participating in both the domestic and public spheres. The obligatory role of women in the domestic sphere is as a wife to her husband and mother to her children. Meanwhile, as a member of the community in matters of muamalah in the public domain, they are punished with an emergency rukhshah. This means that even though it is permissible, women must still follow existing Islamic rules, including when leaving the house they have to cover their private parts, get permission from their husbands and always prioritize the aspect of benefit both for the household and for the community. If it causes more harm to the family then professions outside the home must be abandoned considering something that is an emergency cannot leave things that are mandatory. Keywords: Women, Family, Politics Abstrak: Rumusan masalah yang akan diangkat dalam penelitian ini yaitu: 1.Bagaimana peran politisi perempuan dalam Memelihara keharmonisan rumah tangga di Dewan Pimpinan Daerah Partai Golkar Provinsi Bengkulu? 2.Bagaimana Tinjauan Hukum Islam terhadap peran politisi perempuan dalam Memelihara keharmonisan rumah tangga di Dewan Pimpinan Daerah Partai Golkar Provinsi Bengkulu?Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian hukum yuridis empiris. Penelitian ini menyimpulkan bahwa:1.Berdasarkan hasil penelitian penulis maka dapat disimpulkan bahwa Peran Politisi Perempuan dalam mempertahankan keharmonisan rumah tangga di Dewan Pimpinan Daerah Partai Golkar Provinsi Bengkulu sebagai berikut: Dalam pelayanan dengan suami Ibu Mardensi dan Ibu Mega Sulastri melakukannya dengan intesnsif setiap kali, Walaupun sebagai anggota Legislatif Ibu Mardensi maupun Ibu Mega Sulastri tetap seperti ibu-ibu yang lain seperti menyiapkan sarapan untuk suami dan anak, menyiapkan segala keperluan suami jika ada dinas luar, Untuk setiap hari libur berusaha untuk berwisata keluarga dan memasak makanan sesuai selera anak dan suami, Saling memberikan perhatian dengan memberikan hadiah ulang tahun untuk suami dan Menjalin komunikasi dan bersikap jujur dan terbuka kepada suami dan menciptaskaan suasan yang menyenangkan di dalam keluarga. 2.Tinjauan Hukum Islam Terhadap Peran Politisi Perempuan dalam mempertahankan keharmonisan rumah tangga di Dewan Pimpinan Daerah Partai Golkar Provinsi Bengkulu, Pada dasarnya Islam tidak melarang kaum perempuan untuk ikut berperan baik di ranah domestik maupun di ranah publik. Peran perempuan yang wajib di ranah domestik adalah sebagai istri dari suami dan ibu bagi anak-anaknya. Sedangkan sebagai anggota masyarakat dalam urusan muamalah di ranah publik dihukumi dengan rukhshah darurat. Artinya meskipun diperbolehkan, namun kaum perempuan harus tetap mengikuti aturan-aturan Islam yang ada, diantaranya ketika keluar rumah harus menutup aurat, mendapatkan izin dari suami dan selalu mementingkan segi kemaslahatan baik bagi rumah tangga maupun bagi masyarakat. Apabila lebih banyak kemudaratannya bagi keluarga maka profesi di luar rumah harus ditinggalkan mengingat sesuatu yang darurat tidak boleh meninggalkan hal yang wajib. Kata Kunci : Perempuan, Keluarga,Politi